Implementasi Steganografi Dengan Menggunakan Metode Masking And Filtering Untuk Menyisipkan Pesan Ke Dalam Spectrogram Audio: Indonesia - Kusuma, Permadi; Prayudi, Yudi (Asian Journal of Innovation and Entrepreneurship, 2025)
When sending a message to a specific party and do not want the message to be known by other parties, it is important to avoid information leakage. However, the problem identified is that there is a lack of knowledge to detect audio Ste-ganography which requires technical methods that can read and view secret messages. One method that can be used in steganography is Masking and Filtering. Masking as a media marker on audio that can insert messages. Filtering gives value to the parts that have been given a mark.  This method is one that is often used because it is simple, fast in the data insertion process, and has a large enough storage capacity. The Masking and Filtering method is able to hide messages by inserting them into the audio Spectrogram as a storage medium. The filter is used to ensure that the hidden message is within the previously analyzed frequency range, thus making humans unable to clearly hear the additional audio that has been inserted which is the hidden message.  After the insertion is complete, the audio file is saved, and tests are performed to ensure that the audio quality is not compromised, and the hidden message remains undetected such as making modifications to the stego file to test the robustness and security of the hidden message. Based on research, steganography is difficult to detect by the naked eye, to retrieve messages that have been hidden, it can be done by displaying an audio Spectrogram that contains a secret message. How to see the hidden message using the Audacity application that can see sound waves. The result is that the message embedded in the audio is not damaged even though compression, cutting, and some of the processes carried out in the audio have been carried out.